2021
DOI: 10.3389/fendo.2021.632324
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Acupuncture in Obesity: A Perspective From the Hypothalamus

Abstract: Obesity is a prevalent metabolic disease caused by an imbalance in food intake and energy expenditure. Although acupuncture is widely used in the treatment of obesity in a clinical setting, its mechanism has not been adequately elucidated. As the key pivot of appetite signals, the hypothalamus receives afferent and efferent signals from the brainstem and peripheral tissue, leading to the formation of a complex appetite regulation circuit, thereby effectively regulating food intake and energy homeostasis. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 144 publications
1
26
0
1
Order By: Relevance
“…Specifically, this intervention has the potential to activate the satiety center and modulate appetite by regulating certain hormones, such as insulin and ghrelin [ 57 ]. The appetite-suppressing effect of acupressure has been consistently reported in previous studies [ 58 , 59 , 60 ]. Moreover, it has been reported that acupressure, especially auricular acupressure for 12 weeks, has a significant weight loss effect in overweight and obese people [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 71%
“…Specifically, this intervention has the potential to activate the satiety center and modulate appetite by regulating certain hormones, such as insulin and ghrelin [ 57 ]. The appetite-suppressing effect of acupressure has been consistently reported in previous studies [ 58 , 59 , 60 ]. Moreover, it has been reported that acupressure, especially auricular acupressure for 12 weeks, has a significant weight loss effect in overweight and obese people [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 71%
“…Of the network, AON, COA, and PIR receive projections from the main olfactory bulb (MOB) and accessory olfactory bulb (AOB), and there are mutual projections among the nuclei of AON, OT, COA, PIR, and ENT. We also found that OT emits strong projections to ventromedial hypothalamic nucleus (VMH) and lateral hypothalamic area (LHA), two important nuclei which regulate the feeding behavior ( Steffens et al, 1988 ; Wang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 83%
“…Concerns about these side effects and the need for alternative therapies are the reasons why the demand for TEAM therapies is gradually increasing in obesity treatment. The mechanisms of action of acupuncture in obesity are known to affect the regulation of appetite from the perspective of hypothalamus or a decrease in the expression of leptin and insulin [50] . In herbal medicine, the multi-target, synergistic effect of herbs affects obesity by regulating fat metabolism, hormone level, and energy metabolism through intestinal microflora [51] .…”
Section: Discussionmentioning
confidence: 99%